Optimalisasi Pengembangan Bisnis pada Petani Ikan Ciparay - Utami, Latifa Alda; Ramdan, Ahmad Taufiq Maulana; Wijaya, Fanji; Mubarok, Dadan Abdul Aziz (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
An essential strategic effort to improve community welfare and the productivity of the fishing industry is to optimize the development of fish farmer businesses in Ciparay, Bandung Regency, West Java, which has a lot of potential for cultivating freshwater fish. Fish farmers in this area, however, still face several problems. These include lack of access to advanced technology, knowledge about managing a business, and market limitations. This research aims to find and create the most effective strategy for building a fish farming business in Ciparay. This research uses SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) and Business Model Canvas to find internal and external elements influencing the fish farming business. Apart from field observations and in-depth interviews with fish farmers, data was collected through relevant literature studies. The results of the analysis show that traditional knowledge and extensive experience in fish cultivation are the main strengths of Ciparay fish farmers. In contrast, the main weakness is the difficulty of obtaining technology and capital. The ever-increasing market demand for fresh fish and government support through various aid programs are opportunities that can be exploited. However, there are threats such as climate change and competition with fish products from other countries. The results show that there are several methods that Ciparay fish farmers can use to maximize their business growth. First, increasing product diversification and innovation in fish processing can open up new market opportunities and increase product-added value. Second, increasing access to modern technology through training and technical assistance can help improve product quality and productivity. Third, forming farmer groups or cooperatives can strengthen farmers' bargaining positions and facilitate their access to capital and wider markets. Farmers can gain greater access to markets and capital by implementing stratification strategies